Religious History and the Eighteenth -Century Historian - Young, Brian W. (The historical journal, 2000)
The relationship between intellectual secularization and the writing of academic history has long been one of the major neglected themes in British historiography, and its unexamined presuppositions are explored here in relation to the religious history of the eighteenth century. A great deal of the history of eighteenth-century religion has been written from a confessional standpoint, and this has served further to marginalize discussion of the subject in a period of history concerning which secular interpretations continue to prevail. A reunion of the religious and the secular is a major desideratum in the writing of eighteenth-century history, and this applies not only to historians of religion but also, a fortiori, to political, social, and cultural historians. The perspectives offered by such historians are critically examined, and the need for them to take seriously the integral part of religious history in the broader history of the period is emphasized accordingly.